Neurochemistry (IntechOpen, 2014)
Neurochemistry is a flourishing academic field that contributes to our understanding of molecular, cellular and medical neurobiology. As a scientific discipline, neurochemistry studies the role of chemicals that build the nervous system, it explores the function of neurons and glial cells in health and disease, it discovers aspects of cell metabolism and neurotransmission, and it reveals how degenerative processes are at work in the nervous system. Accordingly, this book contains chapters from a variety of topics that fall into the following broad sections: I. Neural Membranes and Intracellular Signaling, II. Neural Processing and Intercellular Signaling, III. Growth, Development and Differentiation, and IV. Neurodegenerative Diseases. The book presents comprehensive reviews in these different areas written by experts in their respective fields. Neurodegeneration and neuronal diseases are featured prominently and are a recurring theme throughout most chapters. This book will be a most valuable resource for neurochemists and other scientists alike. In addition, it will contribute to the training of current and future neurochemists and, hopefully, will lead us on the path to curing some of the biggest challenges in human health.